2019
DOI: 10.3889/oamjms.2019.397
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Brain Gym on Quality of Sleep, Anxiety in Elderly at Nursing Home Care Case Medan

Abstract: BACKGROUND:The ageing process of human will cause changes in anatomy and physiology. Biologically, ageing is associated with the gradual accumulation of various molecular and cellular damage. Disorders of sleep quality are influenced by several factors, such as the medical condition of illness, stress, anxiety, and others. Brain gym is a collection of simple movements that aim to connect or unite the mind and body.AIM:To find out the effect of brain gym in the quality of sleep and anxiety in the elderly at nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 5 publications
0
15
0
2
Order By: Relevance
“…The strength of the current study is the application of both psychometrics and standardized and validated biological markers in describing stress and anxiety. Previous studies examining the effectiveness of Brain Gym adopted only subjective measures 12,13,14 , in which subjective bias is inevitable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of the current study is the application of both psychometrics and standardized and validated biological markers in describing stress and anxiety. Previous studies examining the effectiveness of Brain Gym adopted only subjective measures 12,13,14 , in which subjective bias is inevitable.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Azizah and colleagues 12 showed an improvement in perceived levels of psychological distress in elderly people after Brain Gym intervention. Effendy and colleagues 13 also examined the effects of Brain Gym on anxiety and quality of sleep in 68 elderly people and they found that 8-week of Brain Gym training could improve sleeping quality and reduce anxiety symptoms in the studied cohort. On the other hand, Voss 14 found no effect of Brain Gym on the level of perceived stress in a group of school-age children.…”
Section: Introductionmentioning
confidence: 99%
“…Adriani., Imran, Mawi,. Amani., and Ilyas 2020,Effendy, Novi, Utami, 2019 have discussed about the function of brain gym [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies show that brain gym is the nonpharmacological treatment for mental health especially in geriatrics. The ageing process is characterized by the loss of progressive physiological integrity, which causes impaired function and this damage leads to various diseases, such as cancer, diabetes, cardiovascular disorders, and neurodegenerative disease (Efffendy et al, 2019). José María Cancela et al conducted a study which represents the ef icacy of brain gym training on cognitive performance and itness level in elderly patient and suggested that Brain Gym can be considered as a useful physical therapy strategy for older adults, since it can have a positive impact on brain func-tioning.…”
Section: Introductionmentioning
confidence: 99%
“…Performing brain gym enhances the neural pathways which provides effective relearning of the movement, reduces stress and depression, improve cognitive perception, adaption of motion patterns and biomechanics of the body. Most importantly brain gym enhance quality of life which is the most focused aspect of the physiotherapy (Efffendy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%